Mineral chemistry, petrology and geochemistry of the Sebago granite-pegmatite system, southern Maine, USA - Wise,M.; Brown,C.D. (Journal of Geosciences, 2010)
The Permian (293 ± 2 Ma) Sebago Pluton is a homogeneous, two-mica granite situated in the Oxford pegmatite field, southwestern Maine. Surrounding the pluton is an area designated as the Sebago Migmatite Domain (SMD) dominated by metapelitic migmatites and diatexites with subordinate intrusions of heterogeneous, two-mica and biotite granites, pegmatitic leucogranites and granitic pegmatites. The Sebago Pluton plus the SMD formerly defined the extent of the Sebago Batholith. Most of the granitic pegmatites and bodies of pegmatitic leucogranites occur either within, or barely outside, the margins of the SMD. The pegmatitic leucogranite facies displays units typical of fertile granites (granites that produce granitic pegmatites) and include; megacrystic graphic K-feldspar, sodic aplite and potassic pegmatite pods hosting rare tourmaline, beryl and columbite-tantalite. Over 100 granitic pegmatite bodies (Sebago Pegmatite Group - SPG) intrude the outer portions of the SMD and neighboring granitoids and metasedimentary rocks. The pegmatite population includes mineralogically simple to complexly zoned pegmatites that are characterized by a LCT-type (Li, Cs and Ta) geochemical signature, extensive replacement of primary zones and gem-bearing miarolitic cavities. Sebago granites are strongly peraluminous and show rare-element enrichment typical of evolved fertile granites (K/Rb = 87-257), Rb/Tl = 10.6-71.3, Ba/Rb = 0.18-5.04, Al/Ga = 1419-1749, Zr/Sn = 1.53-43.9). The SPG shows high levels of Be, Nb > Ta, P, Li and B with subordinate enrichment in Rb and Cs. Moderate to high levels of rare-element fractionation is encountered in pegmatitic K-feldspar (K/Rb ≈ 17, K/Cs ≈ 90, Rb/Tl ≈ 75); muscovite (K/Rb ≈ 6.6, K/Cs ≈ 14.8, Rb/Tl ≈ 127); beryl (Na/Li ≈ 1.77, Cs2O ≈ 3.15 wt. %), garnet [Mn/(Mn + Fe) ≈ 0.60] and manganotantalite and ixiolite/wodginite [Mn/Mn + Fe) ≈ 0.98, Ta/(Ta + Nb) ≈ 0.80-0.93]. Evidence that supports the pegmatitic leucogranites as the likely parent to the SPG includes the close spatial distribution of the pegmatites to the leucogranite bodies, texturally and mineralogically similar units observed within the leucogranite and the neighboring pegmatites plus gradual, yet overlapping, rare-element fractionation from the leucogranites to the associated pegmatites. A few pegmatites (e.g., the Lord Hill pegmatite and amethyst-bearing pegmatites) show NYF tendencies unlike any other pegmatites of the SPG. Differences in fractionation degree, evolution and/or relation to another fertile granite-pegmatite system may be responsible for this apparently anomalous group of pegmatite dikes.
Keywords: granite-pegmatite system; mineral chemistry; petrology; geochemistry; Sebago; southern Maine